Edukasi Bahaya Merkuri bagi Kesehatan Wanita di Kawasan Tambang Emas Kabupaten Lebong Provinsi Bengkulu - Dian Fita Lestari; Fatimatuzzahra Fatimatuzzahra; Eliza Febrianti; Shahnaz Shabrina Wulansari; Vestidhia Yunisya Atmaja (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase public knowledge, especially among women who live around the gold mine in Lebong Regency, about the harmful effects of mercury on health because women who live around gold mines will have a double risk of being exposed to mercury both from mines and from using unsafe cosmetics. The method of implementing this community service activity used the educational method with several stages, including location surveys, coordination with participants, the stage of educational activities, and the evaluation stage by filling out a questionnaire. The partners for this community service activity were women (mothers) who live around the gold mine in Lebong Regency. The results of this community service activity showed that almost all participants still lack information regarding the effects of mercury on health; many did not know that mercury can cause abnormalities in pregnant women which impact the fetus and baby, as well as the impact of damage to the nerves, brain, and other vital organs of the body other. The existence of this service activity could add insight and knowledge to participants. The evaluation results showed that the participants were satisfied with implementing this activity and expect other educational activities to add new insights and knowledge due to limited information.